Social Bandits as Peasants' Protest in Java during the Dutch East Indies Government (1885–1930) - Arfaton, Arfaton; Miftahuddin, Miftahuddin; Gunartati, Gunartati; Kumalasari, Dyah (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
Banditry in Java during the Dutch East Indies period (1885-1930) emerged as a response by peasants to colonial oppression, particularly because of plantation expansion, labor exploitation, low wages, and land rights seizures. This background made banditry not merely a criminal act, but a symbol of social and political resistance. This study aims to determine the background of the emergence of bandits during the Dutch East Indies government, social bandit actions during the Dutch East Indies government in 1885-1930, and the efforts of the Dutch East Indies government in overcoming these bandit actions. This study uses historical research methods by collecting sources (heuristics), verification, interpretation, and historiography. The results of this study are the background of the emergence of Social Bandit actions due to the disappointment and dissatisfaction of peasants with various policies made by the Dutch East Indies government, such as the Forced Cultivation policy, liberal economy, and expansion of plantation companies. The bandits carried out their actions by stealing, burning plantations, and even killing victims. Bandit actions occurred in Surakarta, Yogyakarta, Batavia, Pasuruan, and Probolinggo. To suppress bandit actions, the Dutch East Indies government reorganized the police, held night patrols, and worked with the local government.